2022
DOI: 10.3389/fsufs.2022.992581
|View full text |Cite
|
Sign up to set email alerts
|

Evolving role of synthetic cytokinin 6-benzyl adenine for drought stress tolerance in soybean (Glycine max L. Merr.)

Abstract: The enhanced growth and productivity of soybeans during the past decades were possible due to the application of agrichemicals such as bio-fertilizers, chemical fertilizers, and the use of high yielding, as well as disease resistant transgenic and non-transgenic varieties. Agrichemicals applied as seed primers, plant protectants, and growth regulators, however, had a diminutive significance on growth and productivity improvements across the globe. The utilization of plant growth regulators (PGRs) for vegetativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 106 publications
0
2
0
Order By: Relevance
“…There have been numerous studies demonstrating the vital role of synthetic growth regulators in reducing the harmful effects of water stress. On this regards, Mangena (2022) explain the vital role of synthetic 6-benzyl adenine to increasing drought stress tolerance of soybean, Zhang et al (2020) revealed that white clover's resistance to drought is improved by indole acetic acid, on ascorbic acid and how it affects plant growth and resistance to water stress, Chun et al (2018) on the influence of osmotic stress on proline accumulation in arbuscular mycorrhizal symbiotic plants and Annunziata et al (2019) on glycine betaine and its connections to increased plant growth and survival, ROS scavenging, membrane stability, activation of stress-responsive genes, and buffering of redox potential, but there have not been any studies examining the impact of these natural products (Origanum majorana, Nigella sativa, and Curcurma longa extracts) on drought stress. Accordingly, this study carried out to examine the impact of vivo application of synthetic growth regulators (IAA, BA, ASA, proline, and glycine betaine) on the growth, yield traits and 3 biochemical analysis of sunflower (Helianthus annuus L.) plant, in compared of new biostimulants with the goal to choose a treatment that will be applied fairly to promote sunflower development under water stress.…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 97%
“…There have been numerous studies demonstrating the vital role of synthetic growth regulators in reducing the harmful effects of water stress. On this regards, Mangena (2022) explain the vital role of synthetic 6-benzyl adenine to increasing drought stress tolerance of soybean, Zhang et al (2020) revealed that white clover's resistance to drought is improved by indole acetic acid, on ascorbic acid and how it affects plant growth and resistance to water stress, Chun et al (2018) on the influence of osmotic stress on proline accumulation in arbuscular mycorrhizal symbiotic plants and Annunziata et al (2019) on glycine betaine and its connections to increased plant growth and survival, ROS scavenging, membrane stability, activation of stress-responsive genes, and buffering of redox potential, but there have not been any studies examining the impact of these natural products (Origanum majorana, Nigella sativa, and Curcurma longa extracts) on drought stress. Accordingly, this study carried out to examine the impact of vivo application of synthetic growth regulators (IAA, BA, ASA, proline, and glycine betaine) on the growth, yield traits and 3 biochemical analysis of sunflower (Helianthus annuus L.) plant, in compared of new biostimulants with the goal to choose a treatment that will be applied fairly to promote sunflower development under water stress.…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 97%
“…Cytokinins such as 6-BAP are plant hormones involved in growth and development, the regulation of cell division processes, the delay in senescence, and the regulation of apical dormancy [ 24 , 25 ]. It was reported that the application of 6-BAP in selected crops favors the production of buds [ 26 , 27 ] and the generation of roots and flowers [ 28 , 29 ], in addition to the removal of reactive oxygen species [ 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%